Analisis Faktor Faktor yang Mempengaruhi kepuasan Pengguna Mobile Banking Syariah di Kalangan Generasi Z di Kabupaten Bogor - Hikmatul Aliyah; Abrista Devi; Nurman Hakim (Masyarakat Ekonomi Syariah Bogor, 2025)
The advancement of information technology into digital today makes technology in the banking sector utilized in the marketing process, promotions, to technology-based transaction aids. In the midst of rapid advances in information and communication technology, banks are competing to improve digital services, especially for Islamic banks, One of the electronic banking products that is currently being widely used is mobile banking. Fulfilling customer needs for excellent banking services and being able to generate loyal customers can increase customer satisfaction. This study aims to analyze the factors that influence the satisfaction of Islamic mobile banking users among generation Z in Bogor Regency. This research uses a quantitative approach, where data is collected through questionnaires distributed to 200 respondents who are generation Z sharia mobile banking users in Bogor Regency and then further analyzed using SMART PLS 4.0 with the PLS-SEM method. The factors analyzed in this study include ease of use, perceived benefits, security, price value, and hedonic motivation. The results of the analysis show that ease of use and benefits have no significant effect on the satisfaction of Islamic mobile banking users while security, price value, and hedonic motivation have a significant effect on the satisfaction of Islamic mobile banking users.